Influence of Dietaries Combined Vitamin E and Selenium Powder on Eggs' Fertility and Hatchability in Japanese Quail - Ameen, Mohmood H. M.; Wahhab, Mohammed A.; Kareem, Mohammed TH. (Sulaimani Journal for Pure and Applied Sciences, 2022)
This study was conducted at the Sulaimani Polytechnic University, Kalar Technical College, Veterinary Techniques Department, and animal management farm. The objective of the present study was to show the effect of adding different levels of vitamin E and inorganic Selenium (Sodium selenite) on the fertility and hatchability of Japanese quail from Apr 15 2021 to Jul 15 2021. A total number of 128 birds at 12 weeks old Japanese quail (Coturnix Coturnix Japonica) were used (96 females and 32 males). These birds were randomly divided into four dietary treatment groups (T); each group was equally subdivided into 8 replicate boxes; each replicate box consisted of 1 male (8 males per group) and 3 females (24 females per group). The quails were housed in vertical boxes and raised under similar environmental, managerial, and veterinarian conditions. The four experimental diets were: 0 = the basal diet (control) with no additions, T1 = 1.0 g vitamin E + selenium mixture/kg diet, T2 = 1.5 g vitamin E + selenium mixture/kg diet, T3 = 2 g vitamin E + Selenium mixture/kg diet. The results showed that the quail birds that were fed supplemented diet with vitamin E + selenium had significantly (P<0.05) higher results in fertility and hatchability, and the study indicated a lower significant effect (P < 0.05) in embryonic mortality of eggs and higher significant increments (P < 0.05) in hatchability of Vitamin E+ Selenium supplemented in T2 with females fed as compared with other treatments and control groups. In conclusion, supplementation of vitamin E +selenium to quail diets is an ameliorative tool in fertility and hatchability traits of Japanese quail.
Keywords: Quail; Fertility; Hatchability; Vitamin E and Selenium